Regenerative agriculture augments bacterial community structure for a healthier soil and agriculture - Singh, Indira; Hussain, Meeran; Manjunath, G.; Chandra, Nagasuma; Ravikanth, G. (Frontiers in Agronomy, 2023)
Use of chemical fertilization and pesticides not only harm the environment but also have detrimental consequences on human health. In recent years, there has been a major emphasis worldwide on natural agriculture methods. Regenerative agriculture is known across the world as a combination of nature-friendly farming practices such as no-till, cover cropping, crop-rotation, agro-forestry and use of organic home-based/ farm-based ingredients to revive soil health. In India, a number of farmers are slowly adopting these practices using home-based mixtures and farmyard manure for soil rejuvenation and pest management. In order to evaluate the efficacy of the regenerative agriculture practices, this study compared conventional and regenerative agriculture plots for their soil bacterial and nutrient profiles. Two crops - ragi (Finger millet, an old world cereal eaten in India) and vegetable (tomato/beans), and different lengths (≤3 and >5 years) of regenerative practices were additional metrics considered to understand variabilities due to crop-type and period of application. The regenerative agriculture practices used included mulching, minimal-till, intercropping, crop-rotation, farmyard manure and home-based concoctions. All regenerative practices were effective in bringing about an enrichment for soil bacteria with a more heterogeneous composition. In regenerative vegetable (RV) plots the relative abundance of Actinobacteriota (7.47%/ 6.24%/ 7.02%) and Chloroflexi (9.37%/ 6.63%/ 8.75%) was slightly higher in comparison to conventional vegetable (CV) plots and Barren land (BL) while levels of Acidobacteriota (8.1%/ 9.88%/ 9.62%) was significantly lower. The regenerative ragi (RR) plots saw higher representation of Firmicutes (5.45%/ 2.38%/ 1.45%) and Actinobacteriota (11.53%/ 7.08%/ 7.15%) in comparison to conventional ragi (CR) plots and BL and a reduction in Acidobacteriota (6.91%/ 7.39%/ 9.79%). The RV plots were enriched for Plant Growth Promoting Rhizobacteria (PGPRs) - Pseudomonas sp. (0.51%/ 0.01%/ 0.21%), and RR plots were enriched for Bacillus sp. (1.35%/ 0.95%/ 0.61%), and Mesorhizobium sp. (0.30%/ 0.12%/ 0.21%), which are known to play significant roles in vegetable and ragi growth respectively. Interestingly, long-term regenerative agriculture was able to support good nutrient composition while enhancing Soil Organic Carbon (SOC) levels. In all, the regenerative agriculture practices were found to be effective in improving bacterial community structure and simultaneously improving soil health.